Best practice of transformational leadership among multi-ethnic headteachers of primary schools, Malaysia - Salleh, Mohamad Johdi; Saidova, Parvina (International Organisation of Scientific Research (IOSR), 2013)
The objectives of this study are to examine the best practice of transformational leadership among multi-ethnic Headteachers of various types of primary schools, Malaysia, according to the gender, age, working experience, number of students, ethnic group, academic qualifications, working state, location of the school, and, type of school. The study was based on the survey of one-hundred-seventy-six multi-ethnic Headteachers pursuing a Bachelor of Educational Management programme who were chosen randomly and conveniently from three universities namely the University of Tun Hussein Onn Malaysia (UTHM), University of Malaysia Sabah (UMS), and International Islamic University Malaysia (IIUM). The findings are presented in frequency and percentage form. The result of the descriptive statistics showed that majority of the Multi-Ethnic Headteachers had a positive perception of practicing transformational leadership and they seemed to have an average level on their perception. This could mean that the school Headteachers had a positive attitude toward the importance of practicing all four dimensions of transformational leadership. Especially, the dimension of creating productive school culture was found significant. Noticeably, the dimension of providing intellectual stimulation was perceived least significant by respondents.